Kedudukan Hak atas Tanah Waris Warga Negara Indonesia yang Berpindah Kewarganegaraan - Kadek Hapsari Ika Palupi; Ida Ayu Putu Widiati; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2020)
A person’s citizenship status has an impact on obtaining guarantees of rights from the state. Indonesian citizens are granted the right to obtain ownership rights to land in Indonesia, but not to those who have changed their citizenship status. The case is different if a citizen acquires the rights of ownership over land due to inheritance. In this regard, this study addresses two questions: 1) how is the inheritance rights in Indonesia based on the Civil Code regulated? ) What is the position of inheritance rights of Indonesian a citizen who has changed his/her citizenship status? This study uses a normative legal research method with a statutory approach and a conceptual approach to achieve these goals. The results indicate that the regulation of inheritance rights in Indonesia is realized through the enactment of three types of inheritance law, namely Customary Inheritance Law, Islamic Inheritance Law and Civil Code Inheritance Law. In the Civil Code of Inheritance Law there are groups that distinguish between heirs and wills whose contents shall not conflict with legitieme portie (absolute part) and shall relate to its inheritance which is land. Then, there are other rules that need to be obeyed namely Indonesian Republic Law Number 5 of 1960 concerning Basic Regulations of Agrarian Principles. The status of ownership rights of land of an Indonesian citizen who has changed his/her citizenship status transfers to the state if the said citizen does not transfer the status of his/her land inheritance within one year from his transfer of citizenship.